The secret between the shadow and the soul [compact disc] - Marsalis, Branford (Marsalis Music : OKeh, 2019)
The band's first album since 2016's acclaimed Upward Spiral finds the celebrated ensemble at a new peak, addressing a kaleidoscope of moods with inspiration and group commitment.